Anal squamous intraepithelial lesions among HIV positive and HIV negative men who have sex with men in Thailand. Issue 7 (11th June 2009) - Li, A H; Phanuphak, N; Sahasrabuddhe, V V; Chaithongwongwatthana, S; Vermund, S H; Jenkins, C A; Shepherd, B E; Teeratakulpisarn, N; van der Lugt, J; Avihingsanon, A; Ruxrungtham, K; Shikuma, C; et al.
Abstract : Objectives: To evaluate the prevalence and risk factors of anal squamous intraepithelial lesions (ASIL), the putative anal cancer precursor, in Asian HIV positive and HIV negative men who have sex with men (MSM). Methods: Men who underwent anal Pap smear reported clinical, sociodemographic and behavioural information collected through questionnaire and interview between January 2007 and April 2008. χ 2 and logistic regression were used to evaluate ASIL prevalence and risk factors among HIV positive and HIV negative MSM. Results: Of the 174 MSM (mean age 32.1 years), 118 (67.8%) were HIV positive. Overall, 27% had abnormal anal cytology: 13.2% had atypical squamous cells of undetermined significance (ASC-US), 11.5% had low-grade squamous intraepithelial lesion (LSIL) and 2.3% had high-grade squamous intraepithelial lesion (HSIL). Prevalence of ASIL was higher among HIV positive than HIV negative MSM (33.9% vs 12.5%; p = 0.003). Among HIV positive MSM, 16.1% had ASC-US, 14.4% had LSIL and 3.4% had HSIL and 7.1%, 5.4% and 0% in HIV negative MSM, respectively. Anal condyloma was detected in 22% of HIV positive and 16.1% (9/56) of HIV negative MSM (p = 0.5). In HIV positive MSM, anal condyloma (OR 3.42, 95% CI 1.29 to 9.04; p = 0.01) was a significant risk factor for ASIL. Highly active antiretroviral therapy use and CD4+ T cell count were not associated with ASIL. Conclusions: One-third of HIV positive and 12.5% of HIV negative MSM had ASIL. Thus, as greater numbers of HIV positive MSM live longer due to increasing access to HAART worldwide, effective strategies to screen and manage anal precancerous lesions are needed.